POLICIES TO HELP SMES OVERCOME COVID-19 (Academicia Globe: Inderscience Research, 2022)
Uzbekistan is the most densely populated country in the Central Asian region, with one third of the population under the age of 29 and half residing in rural areas. As 800,000 people under the age of 29 join the labor market every year, job generation is an urgent and challenging priority.